1989
DOI: 10.1111/j.1745-6584.1989.tb01973.x
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical Resistivity of the Vadose Zone — Field Survey

Abstract: An expansion of Archie's law relates the electrical resistivity of the unsaturated zone to pore‐water resistivity, porosity, saturation, electrical matrix conductivity, and lithological constants. With decreasing saturation the effect of the matrix conductivity increases relative to the electrical conduction of the pore fluid. The bulk electrical resistivity depends on water quality and quantity due to its dependence on pore‐water resistivity and porosity. It is also influenced by the hydraulic conductivity du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 9 publications
1
33
0
1
Order By: Relevance
“…Rock resistivity depends on a number of factors such as the amount of water present in fractures, weathering, porosity, fracturing and the degree of saturation [25].With decreasing grain-size and water quality, the resistivity value is decreased. In saturated layers having high resistivity water and small-grain size, the electrical current is not only conducted by the water but also by the grain matrix [26].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Rock resistivity depends on a number of factors such as the amount of water present in fractures, weathering, porosity, fracturing and the degree of saturation [25].With decreasing grain-size and water quality, the resistivity value is decreased. In saturated layers having high resistivity water and small-grain size, the electrical current is not only conducted by the water but also by the grain matrix [26].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…It assumes that the characteristic of the solid phase does not influence the electrical current conduction. Frohlich and Parke (1989) reported that the great practical success of Archie's law was related to the assumed validity of the determined constants on a large range of soils except for clayey soil. Indeed, this relationship was successfully used for water content estimation in numerous studies Zhou et al, 2001).…”
Section: Water Contentmentioning
confidence: 99%
“…The analysis of the vertical electrical sounding data, when accompanied by geological information, can permit the determination of groundwater types (Hallenbach, 1953;Jackson et al, 1978;Koefoed, 1979;Kossinski and Kelly, 1981;Frohlich et al, 1987;El-Waheidi et al, 1992;Kelly and Mares, 1993;Guérin et al, 2001;Frohlich and Urish, 2002;Matias, 2002;Mhamdi et al, 2006) and subsurface structural features of water bearing formations (Töpfer, 1976;Shettigara and Adams, 1989;Zouhri et al, 2004b;Akaolisa, 2006) and the comprehension of the saturated/unsaturated zones (Kelly and Mares, 1993;Frohlich and Parke, 2005;Toto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%